Dinamika Dakwah Komunitas Te Uti Mongaji - Talalu, Taufik R.; Adam, Sumarlin; Yusuf, Indra Dewi Sery; Nasibu, Sulman A. (Academic Journal of Da'wa and Communication, 2023)
In such a dynamic information era, keeping the younger generation's understanding of religion relevant has become increasingly challenging. This challenge is not only about theoretical understanding of religion, but also about the application of Islamic religious values ​​and teachings in everyday life. This research focuses on the dynamics of the "Te Uti Mongaji" community da'wah in Lopo Village, Batudaa Pantai District, Gorontalo Regency in increasing understanding of religious knowledge among Islamic youth. This research uses a qualitative approach. This research uses interview, observation and documentation study data collection techniques. Research findings reveal that this community is not only a provider of religious education, but also a strong agent in shaping teenagers' religious identity. However, challenges such as budget limitations, invalid legal status, and consistent participant attendance are obstacles that need to be overcome.